A Field-Friendly Loop-Mediated Isothermal Amplification (FF-LAMP) method for rapid detection of Nosema bombycis in silkworm, Bombyx mori - V Sivaprasad (University of Modena and Reggio Emilia, 2021)
Pebrine is a destructive disease that exhibits horizontal and vertical transmission and therefore it is the only mandatory quarantine item in sericulture. Here, a field-friendly loop-mediated isothermal amplification (FF-LAMP) method has been developed and validated for the rapid detection of Nosema bombycis, a causative agent of pebrine disease in silkworm, Bombyx mori. FF-LAMP primers were selected and designed for small ribosomal subunit gene and the assay was performed to detect the N. bombycis infection in silkworm. The FF-LAMP reaction was effective at 6 mM MgSO4, 1.4 mM dNTPs at 63 °C. The detection range of LAMP assay was found to be 101 dilutions of N. bombycis spores. Specificity of the primers was tested using DNA isolated from pebrine infected silkworm, pebrine free silkworm and pure N. bombycis by conventional PCR and FF-LAMP assay. Results revealed that the primers were specific to N. bombycis DNA. The FF-LAMP assay was validated in different basic silkworm seed farms with simultaneous microscopic examination of N. bombycis infection. This newly developed method is highly effective, specific, sensitive and rapid in detecting N. bombycis infection, eliminating the DNA purification steps and usage of sophisticated equipment. This method can be used in testing large number of samples making it field friendly method in sericulture industry.